Urinary Corticoid Concentrations Measured by 5 Different Immunoassays and Gas Chromatography‐Mass Spectrometry in Healthy Dogs and Dogs with Hypercortisolism at Home and in the Hospital. (16th July 2014) - Galeandro, L.; Sieber‐Ruckstuhl, N.S.; Riond, B.; Hartnack, S.; Hofmann‐Lehmann, R.; Reusch, C.E.; Boretti, F.S.
<x xml:space="preserve">Abstract</x> Background Determination of the urinary corticoid‐to‐creatinine ratio (UCCR) is an important screening test in the diagnosis of hypercortisolism (HC). However, urinary cortisol metabolites interfere with cortisol measurement in immunoassays, leading to decreased specificity. Gas chromatography‐mass spectrometry (GC‐MS) is considered the gold standard for steroid hormone analysis, because it provides a high level of selectivity and accuracy. Objectives To prospectively compare the UCCR of healthy dogs and dogs with HC determined by 5 different immunoassays and by GC‐MS and to evaluate the influence of veterinary care on UCCR. Animals Twenty healthy dogs; 18 dogs with HC. Methods Urine was collected in the hospital and again after 6 days at home. Three chemiluminescence immunoassays (Access 2, Beckmann; Immulite 2000, DPC Siemens, with and without trichloromethane extraction) and 2 RIAs (Utrecht in house; Access Beckmann) were used. GC‐MS analyses were performed with Agilent 6890N/5973N. Urinary corticoid concentrations were related to urinary creatinine concentrations. Results Immunoassay results were significantly higher compared to GC‐MS results. Evaluation of bias plots and clinical assessment made on the basis of the assay results of each dog indicated substantial disagreement among the assays. Sensitivity varied from 37.5 to 75% and with selected assays was lower in samples from day 6 compared to day 0. GC‐MS was not superior to the immunoassays in discriminating healthy from HC dogs. Conclusions and Clinical Importance Considerable variation must be anticipated comparing different urinary cortisol assays. Establishing an assay‐ and laboratory‐specific reference range is critical when using UCCR.